Elevated Serum Transaminase (SGOT/SGPT) and Sepsis in Burn Patients in a Tertiary Hospital, Surabaya, Indonesia - Saputro, Iswinarno Doso; Zarasade, Lobredia; Kurniawan, Rifqi (Folia Medica Indonesiana, 2022)
Highlights: • There is no correlation between the increase of SGOT and sepsis. • Correlation between the increase of SGPT and sepsis was significant founded. Abstract: Burns trigger hypermetabolic stress reactions that cause inflammatory responses. When there is a sustained or increased hypermetabolic reaction, the inflammatory response can be life-threatening, such as sepsis, and significantly impact hepatic metabolic function. After burns, varying degrees of liver injury are usually associated with burn severity. This study determined the correlation between elevated serum transaminases (SGOT/ SGPT) and sepsis in burn patients at a tertiary hospital of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 1, 2018, to December 31, 2020. This was a descriptive-analytic study with a retrospective cohort design. The data in this study included the demography of burn patients, causes of burns, inhalation trauma, burn severity, increased serum transaminase (SGOT/SGPT), mortality, and sepsis. This study found that the correlation between elevated serum transaminases (SGOT/SGPT) and sepsis was determined using the Spearman-Rho Rank statistical test. Burn patients with sepsis in the hospital were dominated by males (65.2%) and mostly aged 26-55 years (69.6%). The flame was found to be the highest cause of burns (80.4%), burn area above 20% (91.3%), the highest level of severity was major burn (91.3%), and no inhalation trauma (54.3%). In this study, there was an increase in SGOT of 69.6% and SGPT of 78.3%, with a mortality rate of 39.1%, with average inpatient days of 24 days. The correlation test between elevated serum transaminase (SGOT) and sepsis showed an insignificant relationship (p = 0.065, p> 0.05) with a correlation coefficient of 0.200. In contrast, the correlation between elevated serum transaminase (SGPT) and sepsis was significant (p=0.006, p<0.05) with a correlation coefficient of 0.296.